2002
DOI: 10.1063/1.1456441
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponents of inhomogeneous ferromagnets

Abstract: A method for the analysis of temperature and field dependent magnetization data near the Curie temperature T C is devised, which allows the reliable determination of critical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Berger et al 17 found that the breadth of the T C distribu- tion in the inhomogeneous ferromagnet La 1/3 Ca 1/3 MnO 3 depends on field as…”
Section: Paramagnetic-ferromagnetic Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berger et al 17 found that the breadth of the T C distribu- tion in the inhomogeneous ferromagnet La 1/3 Ca 1/3 MnO 3 depends on field as…”
Section: Paramagnetic-ferromagnetic Transitionmentioning
confidence: 99%
“…17 While it is significant that this model can determine critical behavior in systems where the intrinsic broadening due to disorder is comparable to the field broadening, our primary interest is in using it as a means of quantifying disorder.…”
Section: Paramagnetic-ferromagnetic Transitionmentioning
confidence: 99%
“…The broadening is attributed to the distribution of local environments created by disorder. T C cannot be determined accurately from the minimum of dM͑T͒ / dT, and instead is found by fitting M͑T͒ to a distribution of Curie temperatures: [20][21][22] …”
Section: A the Paramagnetic Regimementioning
confidence: 99%
“…We have studied the correlation between the broadening of the isothermal magnetic entropy change and the Curie temperature (T C ) distribution in nanostructured Pr 2 Fe 17 and Nd 2 Fe 17 alloys produced by high-energy ball-milling after milling times of 10, 20, and 40 h. The changes in the microstructure affect the Fe local environments and as a consequence the magnetic interactions, giving rise to T C distributions centered around 285 K and 330 K for the Pr 2 Fe 17 and Nd 2 Fe 17 alloys, respectively. The width of the distributions enlarges (up to 60 K) as the milling-time increases, and consequently, the isothermal magnetic entropy change curves show an extended full width at half maximum.…”
mentioning
confidence: 99%
“…Hence, we could picture the nanostructured powders having a distribution of Fe-Fe interatomic distances around the value for the Bulk alloys giving rise to a distribution of Curie temperature values. 8,9 Then, we describe the temperature dependence of the magnetization M(T) by a superposition of individual power-law functions, according to 17 …”
mentioning
confidence: 99%